Where Tradition Meets Innovation: Ethnoscience, Creativity, and the Future of Project-Based Learning in Higher Education - Muhammad Fuad Sya'ban; Adi Rahmat; Siti Sriyati; Omay Sumarna (Journal of Mathematics Science and Computer Education, 2026)
Indigenous knowledge systems hold untapped potential for fostering creativity in higher education, yet their integration with project-based learning remains systematically unexplored. This study aimed to examine the effectiveness of ethnoscience-integrated project-based learning in developing creativity among higher education students and to map the current research landscape to identify thematic clusters, temporal patterns, and future directions. We employed systematic literature network analysis, combining systematic review with bibliometric analysis. Following PRISMA 2020 guidelines, a total of 49 articles were retrieved and subjected to keyword co-occurrence analysis using VOSviewer, of which six met full inclusion criteria and were systematically reviewed for empirical effectiveness. All six studies demonstrated positive creativity effects (100% directional consistency, p < 0.001) with moderate-to-large effect sizes (d = 0.4–0.6). Three mechanisms emerged: cultural relevance enhancing engagement, traditional knowledge providing novel perspectives, and community connections fostering applied creativity. Bibliometric analysis identified five major research clusters, revealing that ethnoscience integration shows near-complete absence from mainstream literature despite strong empirical support. These findings conclude that ethnoscience-integrated PBL consistently outperforms conventional approaches in both creativity quality and depth of applied problem-solving, suggesting its strong potential as a decolonizing and equity-driven pedagogy for higher education. The implications point toward the urgent need for curriculum redesign that embeds indigenous epistemologies, faculty development in cultural competency, and co-designed, culturally responsive assessment instruments. Looking ahead, the future of ethnoscience, creativity, and PBL in higher education lies in large-scale cross-cultural trials; technology-enhanced ethnoscience learning respecting indigenous data sovereignty; and community-led participatory research that positions indigenous knowledge holders as co-educators and co-researchers.